The Pengaruh Store Atmosphere, Product Assortment dan Price Terhadap Minat Beli di Borma Kota Bandung - Ridwan Nata Atmojo (Jurnal Sekretaris dan Administrasi Bisnis, 2020)
ABSTRACT Borma is a retail business that is very popular with the people of Bandung. Proven by the interest of buying consumers in Borma that can be demonstrated by the number of increasing visitor numbers. There are several factors that affect the buying interest between store atmosphere, product assortment and buying interest. This research aims to determine the influence of store atmosphere, product assortment, and price in a partial and simultaneous interest in Borma Bandung City. The study uses quantitative descriptive research methods and multiple regression analyses. Sampling is done by non-probability sampling method, with the number of respondents in the study is a consumer who has been shopping directly in Borma Bandung City. With the number of respondents as many as 100 people meet the population criteria. Based on the results of the descriptive analysis known that the store atmosphere is in good category with a value of 79.73%, product assortment is in good category with a value of 79.80%, price is in good category with a value of 83.75% and buy interest are in good category with a value of 81.35%. Based on simultaneous hypothesis testing results, and partial store atmosphere, product assortment and price significantly influence the interest of buying in Borma of Bandung City. The coefficient of determination of the determination test shows an influential R Square value of 53.5% while the remaining 46.5% is influenced by other variables not examined in this study. Partially obtained that the variable store atmosphere, product assortment, and price each has an effect of 10.2%, 13.2% and 30% against the interest of buying in Borma di City of Bandung. The advice in this research is Borma Bandung City should re-evaluate the unique criteria for store atmosphere, relationship between products in product assortment, pay attention to the quality of the supplier at the price and have an official account to Interest. Keywords : Store Atmosphere, Product Assortment, Price, Buying Interest